2021
DOI: 10.1001/jamanetworkopen.2020.36297
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interfacility Transfer and Patient and Hospital Characteristics With Thumb Replantation After Traumatic Amputation

Abstract: This cross-sectional study examines associations of interfacility transfer and patient and hospital characteristics with thumb replantation attempts and success after traumatic thumb amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In comparison, Billig et al found that interfacility transfer following traumatic thumb amputation was associated with increased odds of replantation attempt and increased replantation success. 17…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, Billig et al found that interfacility transfer following traumatic thumb amputation was associated with increased odds of replantation attempt and increased replantation success. 17…”
Section: Discussionmentioning
confidence: 99%
“…All studies included in this review concluded that following finger amputation, the odds of replantation attempt and replantation success are significantly less for uninsured patients compared with those with private insurance. 17,[20][21][22][23] In addition, having noncommercial insurance was associated with increased odds of amputation following burn injury. 24 Insurance status has been demonstrated to affect the type of skin graft one will receive following hand burns.…”
Section: Patient-related Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, it occurs at the discretion of the receiving physician and upon approval by an accepting physician after a telephone discussion regarding the needs of the patient and the potential of the receiving hospital to meet those needs. Willingness of a receiving specialist to accept transfer of a patient varies widely by institution, speciality, and individual, as do patient outcomes after transfer 12–14 …”
Section: Introductionmentioning
confidence: 99%
“…Willingness of a receiving specialist to accept transfer of a patient varies widely by institution, speciality, and individual, as do patient outcomes after transfer. [12][13][14] Patients living with Alzheimer's disease and related dementias (ADRD) visit the ED an average of 1.5 times per year, surpassing the number of visits for patients with cancer, ischemic heart disease, or heart failure. 15,16 They are particularly vulnerable to poor outcomes after any care transition, including interhospital transfer, because of medication errors, environmental changes that can negatively impact cognition, and the physical transition itself.…”
Section: Introductionmentioning
confidence: 99%